2023
DOI: 10.3389/fpubh.2023.1096903
|View full text |Cite
|
Sign up to set email alerts
|

Low depression literacy exacerbates the development and progression of depressive mood in Chinese adult social media users during COVID-19: A 3-month observational online questionnaire-based study with multiple cross-sectional analyses

Abstract: BackgroundThe main purpose of this study was to explore the relationship between depression literacy (D-Lit) and the development and progression of depressive mood.MethodsThis longitudinal study with multiple cross-sectional analyses used data from a nationwide online questionnaire administered via the Wen Juan Xing survey platform. Eligible participants were 18 years or older and had subjectively experienced mild depressive moods at the time of their initial enrollment in the study. The follow-up time was 3 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 54 publications
0
2
0
Order By: Relevance
“…A previous study also showed that COVID-19 profoundly affects anxiety levels, impacting patients' psychological wellbeing ( 54 ). A study from China observed that enhancing D-Lit during the pandemic reduced depression, ( 55 ) while another study noted that MHL was negatively correlated with stress and positively correlated with psychological health during the COVID-19 pandemic ( 56 ). Therefore, adequate MHL can not only support individuals in critical situations but also play a crucial role in preventing mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study also showed that COVID-19 profoundly affects anxiety levels, impacting patients' psychological wellbeing ( 54 ). A study from China observed that enhancing D-Lit during the pandemic reduced depression, ( 55 ) while another study noted that MHL was negatively correlated with stress and positively correlated with psychological health during the COVID-19 pandemic ( 56 ). Therefore, adequate MHL can not only support individuals in critical situations but also play a crucial role in preventing mental disorders.…”
Section: Discussionmentioning
confidence: 99%
“…This method allowed us to examine the complex interactions between various biological rhythm components, which is a departure from previous research that focused on individual items or total scores of questionnaires [ 27 , 55 , 59 ]. Another strength is our consideration of potential confounding factors, such as traumatic life events (e.g., post-earthquake mental complications and COVID-19-related experiences), which may have exacerbated mental health challenges and disrupted biological rhythms among children and adolescents [ 46 , 47 , 56 ]. In our analyses, we carefully controlled for the specific effects of these adverse events, including earthquakes and the COVID-19 pandemic, to the greatest extent possible.…”
Section: Strengths and Limitationsmentioning
confidence: 99%